EVALUASI TERHADAP SIKLUS PENDAPATAN DIVISI JASA BENGKEL PT X SERTA PENGENDALIAN INTERNALNYA - SANDRA SALIM, LIEM (: 2303-1719)
Internal control is a process that is coordinated and operated in a company that has the purpose to protect the property of the company, ensuring the reliability and correctness of financial reporting. Internal controls need to be applied in a company with the intent of the goals set by the company. Type of research conducted in the form is case studies on the evaluation and internal controls over the revenue cycle X company. This research use the descriptive research and with secondary data to the system and procedures for all sales activities of the company’s operation by conducting field research with corporate leadership, corporate management, and the employees as well as documentation on the company. Based on research conducted, it can be concluded that the invoices are still to be given a number manually by the staff accounting and there is none job desk separation of service advisor who doubles function as the invoice’s maker and also receive money from invoices sales too. Therefore, this company requires an evaluation and internal control in the earning’s cycle more effective and efficient in their business operation.